A jornada da cidade midiatizada: usos e apropriações em apps sociais de mapas - Bittencourt, Daniel de Andrade (Universidade do Vale do Rio dos Sinos, 2019)
This research discusses the emergence of the Mediated City, an environment composed of five distinct territorialities resulting from uses and appropriations of technologies that become media (FAUSTO NETO, 2010), the geo social apps. The object of the work is inserted in the Mediatization context. Four mobile apps made up the corpus: Waze, Nike+, Strava, and Google Maps. To understand different shades of this complex phenomenon, it was decided to construct a singular methodology, formed in four acts: the Observer Act works Niels Bohr's Notion of Complementarity and Werner Heisenberg's Principle of Uncertainty; The Suspension Act discusses the Indicative Paradigm by Ginzburg (1989) and the contributions of José Luiz Braga (2008) in the Communication for making inferences in the field; the Act of Investigation relies on the ideas of Charles Sanders Peirce and his semantic operators to work on the creation of abductive (new knowledge), deductive (diagrammatic proposition) and inductive (hypothesis confrontation) inferences; The Grounding Act discusses Grounded Theory, by Glaser and Strauss (1967), and its relevance to, from the data collected in the observables, create a theory of its own. The thesis stresses the concept of Serge Proulx (2016) about uses and appropriations and proposes a different topology through the access - consumption - use - adoption - appropriation vector. As a final contribution, the research starts from Milton Santos (1997 and 2008), André Lemos (2007, 2009, 2013) and George Amar (2011) to develop the idea of a Territory Matrix, composed of five interpolated and interdependent dimensions: Materializing Territory, Informational Territory, Interactional Territory, Algorithmic Territory and Symbolic Territory. In their exchanges, the five territorialities configure Affection and Affectation Zones, which interfere in people's perception of the territory they inhabit and, therefore, has reflexes in the daily lives of cities. In a mediatization scenario, it is understood that the user of geo social apps emerges as a territorial codesigner.
Keywords: Midiatização; Cidade midiatizada; Apps sociais de mapas; Usos e apropriações; Mobilidade; Mediatizacion; Mediated city; Geo social apps; Uses and appropriations; Mobility; ACCNPQ::Ciências Sociais Aplicadas::Comunicação